2023
DOI: 10.1002/cb.2164
|View full text |Cite
|
Sign up to set email alerts
|

What was yours is (for now) mine: Prior user knowledge reduces product satisfaction but can improve experiential satisfaction in access‐based consumption

Abstract: With the rise of the sharing economy, more consumers than ever are thinking about products not in terms of ownership, but in terms of access necessary to facilitate experiences. In this paper, we build on prior literature, which distinguished product from experiential satisfaction to explore the role that knowledge of a prior user plays in shaping these two types of satisfaction in access‐based consumption experiences. Across three studies, we demonstrate that product and experiential satisfaction can be affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 82 publications
(121 reference statements)
0
2
0
Order By: Relevance
“…A study found that customers with fixed mindsets purchase products or services with solid brand personalities that enhance their self-image (Shaalan et al, 2023). Those with growth mindsets are likely to accept brand extensions and are more likely to use the services again in case of service failure, based on the assurance of better service being provided next time (Stough and Carter, 2023). Other studies revealed that a growth mindset notably affects customers' consumption behaviors and drives them to buy sustainable food (Kim and Kim, 2023;Rahnama and Popkowski Leszczyc, 2022).…”
Section: Mindsets and Customer Citizenship Behaviormentioning
confidence: 99%
“…A study found that customers with fixed mindsets purchase products or services with solid brand personalities that enhance their self-image (Shaalan et al, 2023). Those with growth mindsets are likely to accept brand extensions and are more likely to use the services again in case of service failure, based on the assurance of better service being provided next time (Stough and Carter, 2023). Other studies revealed that a growth mindset notably affects customers' consumption behaviors and drives them to buy sustainable food (Kim and Kim, 2023;Rahnama and Popkowski Leszczyc, 2022).…”
Section: Mindsets and Customer Citizenship Behaviormentioning
confidence: 99%
“…Conversely, consumers may experience art products without any transfer of ownership (i.e. Bardhi and Eckhardt, 2012; Zhang et al , 2023; Stough and Carter, 2023). The large number of people who visit museums and other art exhibitions each year is recognition that people do not have to own art to appreciate it.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%